PENYULUHAN DAN SKRINING KESEHATAN SEBAGAI UPAYA PENCEGAHAN PTM PADA ANGGOTA DWP UPT PSDA WS BRANTAS KEDIRI - Istiasih, Hermin (Universitas Nusantara PGRI Kediri, 2023)
Currently, the community, especially members of DWP UPT PSDA WS Brantas Kediri are facing an epidemic challenge againt non-communicable diseases, where the main risk factor is an unhealthy lifestyle. PTM which has the highest prevalence in DWP UPT PSDAWS Brantas Kediri namely hypertension, diabetes millitus, high uric acid and cholesterol, all of which cause strokes. Counseling and health screening are the initial stages of assessment for interventions against PTM risk factors. This PKM aims to conduct counseling and health screening to DWP UPT PSDA WS Brantas Kediri about the dangers and prevention of PTM. The implementation of this PKM is divided into two parts, namely health counseling and health screening and the number of members who take part in this activity is 80 person. The results of counseling and health screening that are most at risk of becoming NCDs are cholesterol as much as 17,1%; not exercising regularly 49%; history of stroke in the family as much as 11,3%; besides high blood pressure as much as 13,7%. This health counseling and screening provides health education and prevention efforts against deadly PTM, so it is very important to do this regularly with cross-sector collaboration to support the government in reducing the risk and increasing the prevalence of PTM.